PEDOTRANSFER FUNCTIONS FOR DIGITAL SOIL MAPPING IN TROPICAL REGION: A CASE STUDY OF DIGITAL SOIL MAPPING OF SOIL CARBON AND NITROGEN IN WEST JAVA, INDONESIA - Setyono Hari Adi (Widyariset, 2017)
Pedotransfer functions (PTFs) for the tropical region were developed to model topsoil total carbon and nitrogen variations, by using input parameters of Digital Elevation Model—DEM, Normalized Difference Vegetation Index—NDVI and bioclimatic variables. Puerto Rico dataset was used to develop the model, while West Java, Indonesia was chosen for the model application. Using 22 input parameters derived from the three soil forming factors (relief, vegetation, and climate), the PTF could explain 71% and 66% of the soil total carbon and nitrogen variations, while comparable results were obtained from reduced input parameters (RMSE 3.12% and 0.05% for topsoil total carbon and nitrogen, respectively). This result suggests that application of PTFs to model soil properties variation, especially in the tropical region, could be used to generate reliable pre-assessment information to support decision making in the land productivity improvement plan.